UPAYA CEGAH STUNTING MELALUI PENERAPAN ISI PIRINGKU TERHADAP PENINGKATAN UKURAN LILA PADA REMAJA PUTRI DI MTSN 4 TANAH LAUT - Widya Ningsih, Dina; Maolinda, Winda; Mardiatul Ulfa, Ika (Midwifery And Complementary Care, 2024)
Background: The development of stunting in Indonesia based on the results of the 2019 Indonesian Toddler Nutrition Status Study (SSGBI) noted that the number of stunted toddlers in Indonesia currently reaches 27.67 percent. In overcoming this, it is necessary to treat women who are going to have children early on, namely from a young age with specific nutrition interventions and sensitive nutrition that is carried out in a convergent manner. Preliminary data on LILA young girls at MTSN 4 Tanah Laut found that 15 young girls whose LILA size was below standard, namely <23.5 Objective:. Analyzing the effect of applying the contents of my plate on increasing the size of LILA in young women at MTSN 4 Tanah Laut Methods: This type of research is quantitative research with pre-experimental research methodsResult: The size of LILA young women before being given the contents of my plate was below normal with numbers between 18.5 cm to 22.5 cm and after being given the intervention the contents of my plate, there were 7 people whose LILA size increased between 0.2 cm sd 1 cm and there were 3 people did not increase. The results of the analysis using the t-test obtained a p-value of less than 0.05, namely the result of 0.008Conclusion: There is an effect of giving the contents of my plate on increasing LILA as an effort to prevent stunting, so this needs to be conveyed to adolescents as well as parents about meeting nutritional needs to prevent stunting in the future Keywords: Fill my plate, LILA, stunting.